PAPR Reduction of OFDM Signals by Novel Global Harmony Search in PTS Scheme - Hojjat Salehinejad; Siamak Talebi (International Journal of Digital Multimedia Broadcasting, 2012)
The orthogonal frequency division multiplexing (OFDM) modulation technique is one of the key strategies for multiuser signal transmission especially in smart grids and wind farms. This paper introduces an approach for peak-to-average power ratio (PAPR) reduction of such signals based on novel global harmony search (NGHS) and partial transmit sequence (PTS) schemes. In PTS technique, the data block to be transmitted is partitioned into disjoint subblocks, which are combined using phase factors to minimize PAPR. The PTS requires an exhaustive search over all combinations of allowed phase factors. Therefore, with respect to the fast implementation and simplicity of NGHS technique, we could achieve significant reduction of PAPR.